ASYMMETRIC BEHAVIOR OF COSTS IN BRAZILIAN PUBLICLY TRADED COMPANIES:AN ANALYSIS OF BRAZILIAN COMPANIES LISTED ON BMF&BOVESPA BETWEEN 2000 AND 2015 - Sponchiado, Simone (2018)
The objective of this study was to verify the behavior of the costs in relation to sales revenues in Brazilian companies listed on the BMF&BOVESPA between 2000 and 2015. Through a survey, with 347 companies listed on the BMF&BOVESPA, descriptive, quantitative and documentary, Linear regression, mean and coefficient of variation were used to analyze the behavior of costs and the theory of sticky costs. The results showed that, in general, the companies committed 71.26% of net sales revenue (RLV) to cost of goods sold (CPV) over the 16 years analyzed.